2019
DOI: 10.1002/jemt.23228
|View full text |Cite
|
Sign up to set email alerts
|

Estimating volumes from common carp hepatocytes using design‐based stereology and examining correlations with profile areas: Revisiting a nutritional assay and unveiling guidelines to microscopists

Abstract: Assessing fish liver status is common in aquaculture nutrition assays. This often implies determining hepatocytes profile areas in routine thin (5–7 μm) histological sections. However, there are theoretical problems using planar morphometry in thin sections: inherent sampling cells biases, too small numbers of sampled cells, under/overestimation of size, measuring size as areas when cells are three‐dimensional (3D) entities. The gold standard for assessing/validate cell size is stereology using thick sections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Fish undergoing various types of nutritional stressors, such as feed restriction (Souza et al 2001), unbalanced diets (Rašković et al 2019) and lower fee-ding frequency (Rodrigues et al 2017), or exhibiting nutritional pathologies due to certain plant-derived feed additives (Zakęś et al 2008), were found to exhibit smaller hepatocyte nuclei. Accordingly, the essential oil supplementation at the levels evaluated seem to not have been a stressor in our study, as the measures of hepatocyte nuclear size (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Fish undergoing various types of nutritional stressors, such as feed restriction (Souza et al 2001), unbalanced diets (Rašković et al 2019) and lower fee-ding frequency (Rodrigues et al 2017), or exhibiting nutritional pathologies due to certain plant-derived feed additives (Zakęś et al 2008), were found to exhibit smaller hepatocyte nuclei. Accordingly, the essential oil supplementation at the levels evaluated seem to not have been a stressor in our study, as the measures of hepatocyte nuclear size (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear area (NA) and cytoplasmic area (CA) of liver cells was measured for 100 cells per fish (20 hepatocytes × 5 fields of view × 5 fish per feeding regime; group n = 500), which is the minimal amount required to neglect the error generated by such planar morphometric approach, as suggested by Rašković et al [ 80 ]. The nucleo-cytoplasmic index (NCI) was calculated separately for each cell using the following formula [ 71 ]: NCI = 100 × NA × CA −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Often, new ingredients in fish feeds will not cause significant histopathological alterations but will have an effect on the appearance of cells involved in the absorption or transformation of molecules that originate from the feed, such as enterocytes in the intestine or hepatocytes in the liver, respectively [3]. Their surface area or volume can be determined using various histological techniques, and a decreased size of cells (or their nuclei) is a marker for metabolic and physiological differences of organs in fish that are fed alternative feeds [4]. However, some antinutritional factors in plant-based fish feed have inflammatory effects on the distal intestine of fish, causing enteritis.…”
Section: Fish Nutritionmentioning
confidence: 99%